Lanthanum-calcium-magnesium-nickel-based hydrogen storage alloy containing chromium, method for producing the same, and use thereof
Patent Information
- Application Number
- CN202410546095.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-05-06
AI Technical Summary
Existing superlattice La-Mg-Ni type hydrogen storage alloys have drawbacks such as low hydrogen storage capacity and low plateau pressure, resulting in poor hydrogen storage performance.
By adjusting the elemental composition of the lanthanum-calcium-magnesium-nickel hydrogen storage alloy, introducing chromium, and employing induction melting and strip spinning processes, including melting, heat treatment, and multiple grinding and crushing, the uniformity and structure of the alloy are optimized.
It significantly improved the maximum hydrogen absorption and effective hydrogen release of the hydrogen storage alloy, improved the plateau pressure, and enhanced the overall performance of the alloy.
Smart Images

Figure CN118460882B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen storage alloys, specifically to a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, its preparation method, and its applications. Background Technology
[0002] Currently, nickel-metal hydride (NiMH) batteries are a type of rechargeable battery that has achieved mass production. The AB5 type rare-earth lanthanide hydrogen storage alloy for its negative electrode features a high plateau, easy activation, and good kinetic performance, making it one of the more mature hydrogen storage alloys available. However, its hydrogen storage capacity is only 1.5 wt.%. In contrast, rare-earth superlattice La-Mg-Ni type hydrogen storage alloys offer higher hydrogen storage capacity and lower prices, demonstrating significant research potential.
[0003] For example, CN105369068A discloses a La-Mg-Ni hydrogen storage alloy and its preparation method. The preparation method includes the following steps: melting mixed metal raw materials prepared in a certain proportion to obtain a liquid alloy; spraying the liquid alloy onto a cooling roller for rapid cooling to obtain a rapidly quenched alloy, wherein the surface linear velocity of the cooling roller is 3-8 m / s; and subjecting the rapidly quenched alloy to heat treatment, the heat treatment steps including: under the protection of an inert gas, first holding at 500-600℃ for 1-2 hours, then holding at 700-800℃ for 1-2 hours, and finally holding at 800-900℃ for 2-6 hours to obtain a La-Mg-Ni hydrogen storage alloy with a single type of A2B7 phase.
[0004] For example, CN106854715A discloses a lanthanum-magnesium-nickel AB3-type hydrogen storage alloy containing yttrium and its preparation process. The chemical formula of this hydrogen storage alloy is La. a Y b Mg c Ca d In Ni9, a, b, c, and d represent the atomic ratios between elements, where 0 < a ≤ 0.65, 0 < b ≤ 0.65, 0 < c, 0 < d, and 2.5 ≤ a + b + c + d ≤ 3.5. The preparation process of this hydrogen storage alloy is as follows: Raw materials are weighed according to the chemical formula ratio. First, the non-volatile metals (excluding Mg and Ca) are placed in a copper crucible. Vacuum is drawn → helium is introduced to 0.1 MPa → vacuum is drawn → helium is introduced to 0.1 MPa, and this process is repeated three times. The power is turned on, and the material is dried for 1 minute. Then, the helium pressure is fixed at 0.1 MPa, and the temperature is raised for melting. After all the metals are completely melted, the temperature is cooled to 20°C. The volatile Mg and Ca metals are placed in the crucible, washed three times, dried for 1 minute, and then melted under a helium pressure of 0.1 MPa.
[0005] However, current superlattice La-Mg-Ni type hydrogen storage alloys still have drawbacks such as low hydrogen storage capacity and low plateau pressure, resulting in poor hydrogen storage performance. Summary of the Invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, its preparation method and application, so as to solve the shortcomings of superlattice La-Mg-Ni type hydrogen storage alloys, such as low hydrogen storage capacity and low plateau pressure, and poor hydrogen storage performance.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, wherein the elemental composition of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy is as follows:
[0009] La a Ca b Mg c Ni d Cr e
[0010] Where a = 0.55 - 0.70, b = 0.80 - 1.20, c = 0.80 - 1.10, d = 8.90 - 9.10, e = 0.005 - 0.02.
[0011] The hydrogen storage alloy provided by this invention significantly improves the maximum hydrogen absorption and effective hydrogen release capacity of the alloy material by rationally designing and selecting the elemental composition of the superlattice La-Mg-Ni type hydrogen storage alloy, while also significantly improving the plateau pressure, thus ensuring that the hydrogen storage alloy has good performance.
[0012] As a preferred embodiment of the present invention, the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy has the following elemental composition: a = 0.65-0.70, b = 0.70-0.75, c = 1.00-1.10, d = 9.00-9.10, and e = 0.01-0.02.
[0013] In a second aspect, the present invention provides a method for preparing a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in the first aspect, the method comprising the following:
[0014] The raw materials are prepared according to their elemental composition, and then smelted to obtain a cast alloy.
[0015] The obtained as-cast alloy was encapsulated and then heat-treated to obtain an intermediate alloy.
[0016] The intermediate alloy is subjected to a first grinding, a first crushing, a belt spinning process, a second grinding, and a second crushing to obtain a hydrogen storage alloy.
[0017] As a preferred embodiment of the present invention, the smelting is carried out under a protective atmosphere.
[0018] As a preferred embodiment of the present invention, the melting temperature is 900-2000℃.
[0019] Preferably, the melting time is 90-120 seconds.
[0020] As a preferred embodiment of the present invention, the smelting includes a first smelting and a second smelting performed sequentially.
[0021] Preferably, the temperature of the first melting is 1100-1300℃.
[0022] Preferably, the first melting time is 50-70 seconds.
[0023] Preferably, the temperature of the second melting is 1400-1600℃.
[0024] Preferably, the second melting time is 50-70°C.
[0025] As a preferred technical solution of the present invention, the encapsulation process involves covering the cast alloy with a sheet and then placing it in a tube for vacuuming, followed by injecting protective gas until the relative vacuum inside the tube is -0.1 to -0.07 MPa.
[0026] Preferably, the absolute vacuum level at the end of the vacuuming operation is ≤0.0015Pa.
[0027] As a preferred embodiment of the present invention, the heat treatment holding temperature is 800-1000℃.
[0028] Preferably, the heat treatment holding time is 22-26 hours.
[0029] Preferably, the heating rate for raising the temperature to the holding temperature during heat treatment is 15-20℃ / min.
[0030] As a preferred technical solution of the present invention, the linear speed of the belt-spinning machine in the belt-spinning process is 4-6 m / s.
[0031] Thirdly, the present invention provides an application of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in the first aspect, the application including the preparation of power batteries using the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy.
[0032] Compared with existing technical solutions, the present invention has the following beneficial effects:
[0033] (1) By rationally controlling the ratio of each element, the hydrogen storage capacity and plateau pressure of the hydrogen storage alloy can be increased, thereby increasing the effective hydrogen storage capacity.
[0034] (2) By using induction melting and strip spinning together, the uniformity of the alloy is improved, the platform performance is enhanced, and the overall performance is improved. Attached Figure Description
[0035] Figure 1 This is a hydrogen absorption kinetic diagram of the alloy materials obtained in Examples 1, 2, 1, 2 and 3 of the present invention at 298K;
[0036] Figure 2 These are the PCT curves of Embodiment 1, Embodiment 2 and Comparative Example 1 of the present invention at 298K.
[0037] The present invention will now be described in further detail. However, the examples described below are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims. Detailed Implementation
[0038] To better illustrate the present invention and facilitate understanding of its technical solutions, typical but non-limiting embodiments of the present invention are as follows:
[0039] This embodiment provides a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, wherein the elemental composition of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy is as follows (atomic ratio):
[0040] La a Ca b Mg c Ni d Cr e
[0041] Where a = 0.55 - 0.70, b = 0.80 - 1.20, c = 0.80 - 1.10, d = 8.90 - 9.10, e = 0.005 - 0.02.
[0042] In this invention, the element La in the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy has a value α of 0.55-0.70, for example, it can be 0.55, 0.56, 0.57, 0.58, 0.59, 0.6, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69 or 0.70, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0043] In this invention, the elemental composition of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy has a corresponding value b of 0.80-1.20, for example, it can be 0.80, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1.00, 1.02, 1.04, 1.06, 1.08, 1.10, 1.12, 1.14, 1.16, 1.18 or 1.20, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0044] In this invention, the elemental composition of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy has a corresponding Mg element value c of 0.80-1.10, for example, it can be 0.80, 0.82, 0.84, 0.86, 0.88, 0.90, 0.92, 0.94, 0.96, 0.98, 1, 1.02, 1.04, 1.06, 1.08 or 1.10, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0045] In this invention, the elemental composition of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy has a corresponding Ni element value d of 8.90-9.10, such as 8.90, 8.92, 8.94, 8.96, 8.98, 9.00, 9.02, 9.04, 9.06, 9.08 or 9.10, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0046] In this invention, the Cr element in the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy has a corresponding value e of 0.005-0.02, for example, it can be 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019 or 0.02, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0047] Specifically, in the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, the elemental composition is a = 0.65-0.70, b = 0.70-0.75, c = 1.00-1.10, d = 9.00-9.10, and e = 0.01-0.02.
[0048] Furthermore, the present invention provides a method for preparing a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described above, the preparation method comprising the following steps:
[0049] The raw materials are prepared according to their elemental composition, and then smelted to obtain a cast alloy.
[0050] The obtained as-cast alloy was encapsulated and then heat-treated to obtain an intermediate alloy.
[0051] The intermediate alloy is subjected to a first grinding, a first crushing, a belt spinning process, a second grinding, and a second crushing to obtain a hydrogen storage alloy.
[0052] In this invention, the ingredients are powders or alloy particles corresponding to each element according to the composition. If it is a single metal powder, when loading it into the smelting equipment, Mg powder is placed at the bottom, followed by Ca powder, then La powder, and Ni powder is placed at the top. Cr powder is sprinkled on the surface of the material during loading to avoid excessive changes in composition due to material burn-off.
[0053] In the smelting process, a vacuum is first drawn to an absolute vacuum level, and then a protective gas is introduced until the relative pressure is ≤-0.01MPa.
[0054] Specifically, the absolute vacuum level at the end of the vacuuming process is ≤0.0015Pa, for example, it can be 0.0015Pa, 0.0014Pa, 0.0013Pa, 0.0012Pa, 0.001Pa, 0.0008Pa, 0.0006Pa, 0.0004Pa, 0.0002Pa or 0.0001Pa, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0055] Specifically, the melting is carried out under a protective atmosphere;
[0056] In this invention, the protective atmosphere during the smelting process is used to ensure that the smelted product meets the design requirements and to prevent the entry of gaseous impurity elements such as oxygen and nitrogen. The protective atmosphere can be selected from inert gases such as helium, neon, argon, etc.
[0057] Specifically, the melting temperature is 900-2000℃, for example, it can be 900℃, 950℃, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, 1600℃, 1700℃, 1800℃, 1900℃ or 2000℃, etc., but is not limited to the listed values. Other unlisted values within this range are also acceptable.
[0058] Specifically, the melting time is 90-120s, for example, it can be 90s, 92s, 94s, 96s, 98s, 100s, 102s, 104s, 106s, 108s, 110s, 112s, 114s, 116s, 118s or 120s, etc., but is not limited to the listed values. Other unlisted values within this range are also acceptable.
[0059] Specifically, the smelting includes a first smelting and a second smelting performed sequentially;
[0060] The first melting temperature is 1100-1300℃, for example, it can be 1100℃, 1120℃, 1140℃, 1160℃, 1180℃, 1200℃, 1220℃, 1240℃, 1260℃, 1280℃ or 1300℃, etc., but is not limited to the listed values. Other unlisted values within this range are also acceptable.
[0061] The first melting time is 50-70s, for example, it can be 50s, 52s, 54s, 56s, 58s, 60s, 62s, 64s, 66s, 68s or 70s, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0062] The second melting temperature is 1400-1600℃, for example, it can be 1400℃, 1420℃, 1440℃, 1460℃, 1480℃, 1500℃, 1520℃, 1540℃, 1560℃, 1580℃ or 1600℃, etc., but is not limited to the listed values. Other unlisted values within this range are also acceptable.
[0063] The second melting time is 50-70℃, for example, it can be 50℃, 52℃, 54℃, 56℃, 58℃, 60℃, 62℃, 64℃, 66℃, 68℃ or 70℃, but is not limited to the listed values. Other unlisted values within this range are also acceptable.
[0064] Specifically, the encapsulation process involves covering the cast alloy with a sheet and then placing it in a tube for vacuuming. Afterward, a protective gas is introduced until the relative vacuum level inside the tube is -0.1 to -0.07 MPa. For example, this could be -0.1 MPa, -0.098 MPa, -0.096 MPa, -0.094 MPa, -0.092 MPa, -0.09 MPa, -0.088 MPa, -0.086 MPa, -0.084 MPa, -0.082 MPa, -0.08 MPa, -0.078 MPa, -0.076 MPa, -0.074 MPa, -0.072 MPa, or -0.07 MPa, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0065] Specifically, the absolute vacuum level at the end of the vacuuming operation is ≤0.0015Pa, for example, it can be 0.0015Pa, 0.0014Pa, 0.0013Pa, 0.0012Pa, 0.001Pa, 0.0008Pa, 0.0006Pa, 0.0004Pa, 0.0002Pa or 0.0001Pa, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0066] In this invention, the encapsulation process can be replaced by any encapsulation process in the art, as long as it can ensure that the as-cast alloy can be subjected to heat treatment in the encapsulated environment.
[0067] Specifically, the heat treatment holding temperature is 800-1000℃, for example, it can be 800℃, 820℃, 840℃, 860℃, 880℃, 900℃, 920℃, 940℃, 960℃, 980℃ or 1000℃, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0068] Specifically, the heat treatment holding time is 22-26 hours, for example, it can be 22 hours, 22.5 hours, 23 hours, 23.5 hours, 24 hours, 24.5 hours, 25 hours, 25.5 hours or 26 hours, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0069] Specifically, the heating rate for raising the temperature to the holding temperature during heat treatment is 15-20℃ / min, for example, it can be 15℃ / min, 15.5℃ / min, 16℃ / min, 16.5℃ / min, 17℃ / min, 17.5℃ / min, 18℃ / min, 18.5℃ / min, 19℃ / min, 19.5℃ / min or 20℃ / min, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.
[0070] In this invention, after the heat treatment is completed, the furnace is cooled to room temperature, such as 20-35°C.
[0071] Specifically, the linear speed of the belt-spinning machine in the belt-spinning process is 4-6 m / s, for example, it can be 4 m / s, 4.2 m / s, 4.4 m / s, 4.6 m / s, 4.8 m / s, 5 m / s, 5.2 m / s, 5.4 m / s, 5.6 m / s, 5.8 m / s or 6 m / s, etc., but is not limited to the listed values. Other unlisted values within this range are also acceptable.
[0072] In the preparation process provided by this invention, the hydrogen storage performance of the hydrogen storage alloy is improved by combining heat treatment and strip spinning treatment, so that the resulting hydrogen storage alloy has a high and flat hydrogen absorption and desorption plateau pressure, and thus has a high hydrogen absorption and desorption capacity.
[0073] Furthermore, the present invention provides a power battery, which is prepared using the aforementioned chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy.
[0074] To illustrate the superior hydrogen storage performance of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy provided by this invention, a practical example is given below:
[0075] Example 1
[0076] This embodiment provides a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, with the elemental composition having an atomic ratio of La. 0.65 CaMgNi9Cr 0.01 The preparation process is as follows:
[0077] 30g of ingredients were prepared according to the elemental composition of the target alloy. A vacuum induction furnace was first evacuated to a vacuum level of 1.5 × 10⁻⁶. -3 Argon gas was introduced to -0.01 MPa for melting (melting at 1200℃ for 60s, then at 1500℃ for 60s); the melted alloy ingot was sealed using a sealing machine, with the sealing tube filled with inert argon gas at a pressure of -0.08 MPa; the sealed alloy was then heat-treated under the following conditions: heating rate 6℃ / min, holding temperature 950℃, time 24h, followed by natural cooling; finally, the heat-treated alloy was ground and crushed into blocks, then spun into sheets (linear speed 5m / s) to obtain alloy sheets. The alloy sheets were then mechanically ground to remove oxide scale, mechanically crushed, and sieved to 100 mesh to obtain alloy samples.
[0078] The obtained alloy samples were tested for hydrogen storage performance under a hydrogen pressure of 9 MPa and a temperature of 100 °C. The test results are detailed in Table 1.
[0079] Example 2
[0080] This embodiment provides a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, which differs from Example 1 only in that the elemental composition is in the atomic ratio of La. 0.67 Ca 0.96 Mg 0.95 Ni 9.02 Cr 0.015 .
[0081] The obtained alloy samples were tested for hydrogen storage performance at 9 MPa hydrogen pressure and 100 °C. The results are detailed in Table 1.
[0082] Example 3
[0083] The only difference from Example 1 is that the elemental composition of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy is in the atomic ratio of La. 0.55 Ca 1.03 Mg 1.07 Ni 8.97 Cr 0.005 .
[0084] The obtained alloy samples were tested for hydrogen storage performance at 9 MPa hydrogen pressure and 100 °C. The results are detailed in Table 1.
[0085] Comparative Example 1
[0086] According to the composition of the target alloy, La 0.65 CaMgNi9Cr 0.05 Prepare 30g of ingredients, then use a vacuum induction furnace to first evacuate to 1.5×10⁻⁶. -3 Argon gas was introduced to -0.01 MPa for melting (melting at 1200℃ for 60s, then at 1500℃ for 60s); the melted alloy ingot was sealed using a sealing machine, with the sealing tube filled with inert argon gas at a pressure of -0.08 MPa; the sealed alloy was then heat-treated under the following conditions: heating rate 6℃ / min, holding temperature 950℃, time 24h, followed by natural cooling; finally, the heat-treated alloy was ground and crushed into blocks, then spun into sheets (linear speed 5m / s) to obtain alloy sheets. The alloy sheets were then mechanically ground to remove oxide scale, mechanically crushed, and sieved to 100 mesh to obtain alloy samples.
[0087] The obtained alloy samples were tested for hydrogen storage performance at 9 MPa hydrogen pressure and 100 °C. The results are detailed in Table 1.
[0088] Comparative Example 2
[0089] The only difference from Example 1 is that in step (2), the melting is carried out at 1500°C for 120 seconds.
[0090] The obtained alloy samples were tested for hydrogen storage performance at 9 MPa hydrogen pressure and 100 °C. The results are detailed in Table 1. Analysis showed that only a small amount of superlattice structure alloy was formed, resulting in poor hydrogen storage performance.
[0091] Comparative Example 3
[0092] The only difference from Example 1 is that the heat treatment temperature in step (4) is 1500°C.
[0093] The obtained alloy sample was tested for hydrogen storage performance at 9 MPa hydrogen pressure and 100℃. The results are detailed in Table 1. Analysis showed that the alloy structure was damaged due to excessive heat treatment temperature, and a large amount of Mg and Ca volatilized, resulting in poor hydrogen storage performance.
[0094] Comparative Example 4
[0095] The only difference from Example 1 is that the heat treatment temperature in step (4) is 500°C.
[0096] The obtained alloy sample was tested for hydrogen storage performance at 9 MPa hydrogen pressure and 100 °C. The results are detailed in Table 1. Analysis revealed that the hydrogen storage performance deteriorated because the heat treatment temperature was too low and the phase transformation was incomplete.
[0097] Comparative Example 5
[0098] According to the composition of the target alloy: La2CaMgNi3Cr 0.01 Prepare 30g of ingredients, then use a vacuum induction furnace to first evacuate to 1.5×10⁻⁶. -3 Argon gas was introduced to -0.01 MPa for melting (melting at 1200℃ for 60s, then at 1500℃ for 60s); the melted alloy ingot was sealed using a sealing machine, with the sealing tube filled with inert argon gas at a pressure of -0.08 MPa; the sealed alloy was then heat-treated under the following conditions: heating rate 6℃ / min, holding temperature 950℃, time 24h, followed by natural cooling; finally, the heat-treated alloy was ground and crushed into blocks, then spun into sheets (linear speed 5m / s) to obtain alloy sheets. The alloy sheets were then mechanically ground to remove oxide scale, mechanically crushed, and sieved to 100 mesh to obtain alloy samples.
[0099] The obtained alloy samples were tested for hydrogen storage performance at 9 MPa hydrogen pressure and 100 °C. The results are detailed in Table 1. Analysis showed that the hydrogen storage capacity decreased, the plateau pressure decreased, and the overall hydrogen storage performance declined.
[0100] Comparative Example 6
[0101] The only difference from Example 1 is that the vacuum sealing and heat treatment processes are not performed.
[0102] The obtained alloy samples were tested for hydrogen storage performance under a hydrogen pressure of 9 MPa and a temperature of 100 °C. The results are detailed in Table 1. Analysis revealed that the as-cast alloy had an inhomogeneous phase structure and coarse grains, resulting in a significant reduction in hydrogen absorption capacity and a deterioration in hydrogen storage performance.
[0103] Comparative Example 7
[0104] The only difference from Example 1 is that the belt-swinging process is not performed.
[0105] The obtained alloy sample was tested for hydrogen storage performance under a hydrogen pressure of 9 MPa and a temperature of 100 °C. The results are detailed in Table 1. Analysis revealed that the alloy elements segregated, resulting in poor uniformity and affecting the overall hydrogen storage performance.
[0106] Table 1
[0107]
[0108]
[0109] In this invention, wt% refers to the percentage content by mass.
[0110] Furthermore, the hydrogen absorption kinetics of the alloy materials obtained in Examples 1, 2, 1, 2, and 3 of this invention at 298 K, and the PCT performance of Examples 1, 2, and 1 at 298 K, are detailed in the following results: Figure 1 and Figure 2 ;Depend on Figure 1 and Figure 2 It is known that a suitable Cr content can improve the overall performance of hydrogen storage alloys. When the Cr content is too high, the hydrogen storage capacity decreases slightly, the platform performance deteriorates, and the effective hydrogen storage capacity decreases. A reasonable heating process can significantly improve the hydrogen storage performance of hydrogen storage alloys. For superlattice hydrogen storage alloys, high-temperature annealing above 1000℃ will lead to structural damage and deterioration of alloy performance.
[0111] As can be seen from the results of the above embodiments and comparative examples, the hydrogen storage alloy provided by the present invention, through the rational design and selection of the elemental composition of the superlattice La-Mg-Ni type hydrogen storage alloy, significantly improves the maximum hydrogen absorption and effective hydrogen release of the alloy material, while also significantly improving the plateau pressure, thus ensuring that the hydrogen storage alloy has good performance.
[0112] The present invention is described in detail through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for the components used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0113] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0114] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0115] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, characterized in that, The elemental composition of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy, in atomic ratios, is as follows: Day a Approx b Mg c Ni d Cr e Where a = 0.55 - 0.70, b = 0.80 - 1.20, c = 0.80 - 1.10, d = 8.90 - 9.10, e = 0.005 - 0.02; The chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy is prepared by the following method, which includes: preparing materials according to the elemental composition, followed by melting to obtain a cast alloy; The obtained as-cast alloy was encapsulated and then heat-treated to obtain an intermediate alloy. The intermediate alloy is subjected to a first grinding, a first crushing, a belt spinning process, a second grinding, and a second crushing to obtain a hydrogen storage alloy.
2. The chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 1, characterized in that, The chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy has the following elemental composition: a=0.65-0.70, b=0.70-0.75, c=1.00-1.10, d=9.00-9.10, e=0.01-0.
02.
3. A method for preparing a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 1 or 2, characterized in that, The preparation method includes the following: The raw materials are prepared according to their elemental composition, and then smelted to obtain a cast alloy. The obtained as-cast alloy was encapsulated and then heat-treated to obtain an intermediate alloy. The intermediate alloy is subjected to a first grinding, a first crushing, a belt spinning process, a second grinding, and a second crushing to obtain a hydrogen storage alloy.
4. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 3, characterized in that, The melting is carried out under a protective atmosphere.
5. The preparation method according to claim 3, characterized in that, The melting temperature is 900-2000℃.
6. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 3, characterized in that, The melting time is 90-120 seconds.
7. The preparation method according to claim 3, characterized in that, The smelting process includes a first smelting and a second smelting, performed sequentially.
8. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 7, characterized in that, The temperature of the first smelting is 1100-1300℃.
9. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 7, characterized in that, The first melting time is 50-70 seconds.
10. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 7, characterized in that, The second melting temperature is 1400-1600℃.
11. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 7, characterized in that, The second melting time is 50-70℃.
12. The preparation method according to claim 3, characterized in that, The encapsulation process involves encapsulating the cast alloy with tantalum sheets and then placing it in a tube for vacuuming. After that, protective gas is introduced until the relative vacuum inside the tube is -0.1 to -0.07 MPa.
13. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 12, characterized in that, The absolute vacuum level at the end of the vacuuming operation is ≤0.0015Pa.
14. The preparation method according to claim 3, characterized in that, The heat treatment holding temperature is 800-1000℃.
15. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 3, characterized in that, The heat treatment holding time is 22-26 hours.
16. The method for preparing the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 3, characterized in that, The heating rate from the heat treatment temperature to the holding temperature is 15-20℃ / min.
17. The preparation method according to claim 3, characterized in that, The linear speed of the belt-spinning machine in the belt-spinning process is 4-6 m / s.
18. The use of a chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy as described in claim 1 or 2, characterized in that, The applications include the use of the chromium-containing lanthanum-calcium-magnesium-nickel hydrogen storage alloy to prepare power batteries.
Citation Information
Patent Citations
La-Mg-Ni hydrogen storage alloy and preparation method thereof
CN105369068A
Lanthanum-magnesium-nickel-system AB3 type hydrogen-storage alloy containing elemental yttrium and preparation process thereof
CN106854715A
Hydrogen-absorbing alloy and nickel-hydrogen storage battery
CN102203986A
New hydrogen storage alloy and hydrogen electrode using the alloy
JP1999217643A
